Unconventional monetary policy, leverage & default dynamics - Edoardo Palombo (Queen Mary University of London, School of Economics and Finance, 2020)
The objective of this paper to investigate the effectiveness of credit easing policy in mitigating the economic fallout from a financial recession using a model that can account for the observed default and leverage dynamics during the financial crisis of 2007. A general equilibrium model is developed with a financial sector and endogenous asset defaults able to account for the observed default and leverage dynamics. Following an adverse aggregate shock, banks deleverage through two channels: (i) higher non-performing loans provisions, and (ii) lower the marginal return of assets. Credit policy is modelled as an expansion of the central bank's balance sheet countering the disruption in private financial intermediation. Unconventional monetary policy, namely credit easing policy, is shown to be ineffective in mitigating the effects of a financial crisis due to its crowding out effect on the private asset market. Other non-monetary policy tools such as credit subsidies and their efficacy considered.
Keywords: E20; E32; E44; E52; E58; 330; unconventional monetary policy; credit easing; credit subsidies; financialfrictions; default; leverage; financial sector